2002
DOI: 10.1046/j.1365-2141.2002.03532.x
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting long‐term outcome after allogeneic haematopoietic stem cell transplantation for acute myelogenous leukaemia: a retrospective study of 172 adult patients reported to the Austrian Stem Cell Transplantation Registry

Abstract: Summary. Between 1982 and 2000, 172 patients with acute myelogenous leukaemia (AML) received haematopoietic stem cell transplants (SCT) from related (n = 132) or unrelated (n = 40) donors at four Austrian transplant centres and their results were reported to the Austrian Stem Cell Transplantation Registry. Conditioning for SCT consisted of cyclophosphamide and total body irradiation in 156 (91%) patients. Graft‐versus‐host disease (GVHD) prophylaxis was with standard cyclosporine and methotrexate in 95 (55%) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
0
9

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 41 publications
2
28
0
9
Order By: Relevance
“…8,27,28 In the multivariate analysis for OS, age X45 years correlated with decreased survival. The risk of death increased by a factor of 1.57 (57%) per decade.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…8,27,28 In the multivariate analysis for OS, age X45 years correlated with decreased survival. The risk of death increased by a factor of 1.57 (57%) per decade.…”
Section: Discussionmentioning
confidence: 97%
“…Currently recognized risk factors associated with worse outcome include disease status at the time of SCT, older age, and the development of graft-versus-host disease (GVHD). 8 For patients transplanted in CR1, cytogenetic pattern is also a significant predictor of outcome. [4][5][6][7][9][10][11][12] We were interested in evaluating these factors, as well as determining whether quantification of residual disease at the time of transplant was correlated with outcome.…”
mentioning
confidence: 99%
“…[2][3][4][5] Other currently recognized risk factors associated with a worse outcome include older age and development of acute or chronic GVHD. [6][7][8] The aim of this single-center retrospective study was to review the clinical characteristics and evaluate the potential predictors of RFS and OS in unrelated vs sibling donor HCT. Therefore, we analyzed the data of 92 consecutive adult patients with AML and myelodysplastic syndrome (MDS) undergoing their first peripheral blood-derived HCT from related or unrelated donors at the University of Freiburg Medical Center between 1996 and 2006 after treatment with a uniform preparative regimen consisting of high-dose oral BU and CY.…”
Section: Introductionmentioning
confidence: 99%
“…[25][26][27][28][29][30][31] It has been the practice of this center to use one-antigen HLA-mismatched donors for patients with both standard-and high-risk disease using the same NST conditioning regimen and GVHD prophylaxis as their counterparts from HLAidentical sibling donors. Anasetti et al 32 found that overall SV was not compromised in the 119 recipients of oneantigen HLA-mismatched BMT when compared to a cohort of 967 recipients of HLA-matched sibling transplants.…”
Section: Discussionmentioning
confidence: 99%